A Survey on Coverage Problem in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
A wireless sensor network (WSN) is a composed group of a small tiny battery-equipped device capable of sensing, communication and computation which can be scattered over a vast region for the purpose of detecting or monitoring region perfectly. Sensing coverage and network connectivity are two of the most fundamental problem in WSNs. In WSN is usually defined as a measure of how well the sensing field is monitored or sensors are able to observe the physical space. Connectivity can be defined as the ability of the sensor to reach the data sink. Finding an optimal deployment strategy that provides high degree of coverage with network connectivity is extremely challenging. Therefore, maximizing network coverage as well as maintaining network connectivity using the resources constrained node is a non-trivial problem. In this survey article, we classify the coverage problem; analyze the relationship between coverage and connectivity and research challenges and existing problem in this area.